Lingkungan Sosial Budaya dan Persepsi Pelanggan terhadap Pengobatan Luar Puskesmas (Kasus di Kota Kotamobagu dan Kabupaten Bolaang Mongondow Utara, Provinsi Sulawesi Utara) - Mokoginta, Mutu B; Sugihen, Basita Ginting; Susanto, Djoko; Asngari, Pang S (Jurnal Penyuluhan, 2015)
Social cultural environment and Clients perception to the traditional health services considered as two important aspects. Social culture environment measured by social culture values and locality wisdom aspects. Clients perception to the traditional health services measured by perception to traditional mid-wife and perception to the traditional health service. Social culture environment that oriented to the health service has a high category, on the other hand, clients perception to the traditional health services has a middle category. Extention education is needed to improve the client’s behavior. Keywords: Social cultural environment, Clients perception, the traditional health services